In-service Teachers’ Perceptions of Teaching Speaking in English Language Classes - Bhandari, Bhim Lal (English Language Teaching Perspectives, 2023)
Speaking is a significant productive language skill that can be acquired while studying English as a foreign language. It has been one of the main problems teachers have had to deal with. This article aims at exploring perceptions of in-service English language teachers and the problems they encounter in teaching speaking in English classes. For this purpose, I selected four English language instructors purposively from four public schools as research participants. An unstructured interview was employed to gather the necessary data for the purpose. The study was conducted using a narrative inquiry method and the social constructivism theoretical framework. The research findings showed that English language teachers had favourable perceptions about teaching speaking; however, teaching speaking was not satisfactory at the secondary level as it was neglected by the teachers. In addition, immediate correction by the teacher, their poor competency, lack of resources in schools, insufficient interaction with the students, and lack of co-relation between English and Nepali sounds in English were the major problems of speaking. Furthermore, the study implies that the learners need adequate exposure and regular training to the teachers in speaking. To guarantee the quality of the exam, physical facilities must be enhanced, and students' speaking abilities must be made effective through the reform of the current testing system. The study can be helpful in the improvement of teaching speaking skills in the context of Nepal.